VIOLENCE IN SAME-SEX RELATIONSHIPS AMONG ADOLESCENTS - Silva, Lygia Maria Pereira da; Silva, Gabriela Wanderley da; Silva, Mayara Santana da; Cardoso, Mirian Domingos; Santos, Taciana Mirella Batista dos; Beserra, Maria Aparecida (Cogitare Enfermagem, 2024)
Objective: to describe the profile of violence in same-sex relationships among adolescents in the state of Pernambuco-Brazil, reported between 2017 and 2021. Method: The sample consisted of adolescents aged between 10 and 19 (n=925), selected according to their sexual orientation. Data extracted from the individual notification forms for interpersonal/self-inflicted violence in the Notifiable Diseases Information System. Descriptive statistics and Pearson’s chi-square analysis of proportions were carried out. Results: victims were aged 15-19 (61.8%), male (93.9%), brown (77.5%), had up to eight years of schooling (51.7%) and lived in urban areas (77.2%). Most of the aggressors were male, boyfriends, and/or spouses. Sexual, physical, and psychological violence predominated. Conclusion: a profile of violence in same-sex relationships was drawn up, showing that men were the most likely to suffer and practice violence.